Deistvuiushchie litsa . Deistvuiushchie litsa . Cast of Characters . Действующие лица - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. "The Story of One Family": The documentary shows children in boarding schools and foster families focusing on the story of a family with 6 adopted children. "История одной семьи": Документальный фильм о детях в интернатах и приемных семьях. Фильм рассказывает в частности о семье, в которой живет 6 приемных детей.